2015
DOI: 10.3389/fnbeh.2015.00076
|View full text |Cite
|
Sign up to set email alerts
|

Male mice song syntax depends on social contexts and influences female preferences

Abstract: In 2005, Holy and Guo advanced the idea that male mice produce ultrasonic vocalizations (USV) with some features similar to courtship songs of songbirds. Since then, studies showed that male mice emit USV songs in different contexts (sexual and other) and possess a multisyllabic repertoire. Debate still exists for and against plasticity in their vocalizations. But the use of a multisyllabic repertoire can increase potential flexibility and information, in how elements are organized and recombined, namely synta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
319
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(342 citation statements)
references
References 67 publications
(101 reference statements)
20
319
3
Order By: Relevance
“…Conversely, if we apply Sheehan's definition to the songs of mice, the question arises: can we identify a "voice-machine complex" there as well? Arguably, this is precisely what the 2015 study mentioned at the outset (Chabout et al 2015) revealed: namely that the songs of mice are not, in fact, simply mechanical and repetitive, but rather vary according to complex social cues and environmental circumstances. Moreover, these ultrasonic vocalizations seem to comprise both innate and learned elements (cf.…”
Section: Who Is Squeaking?mentioning
confidence: 82%
See 1 more Smart Citation
“…Conversely, if we apply Sheehan's definition to the songs of mice, the question arises: can we identify a "voice-machine complex" there as well? Arguably, this is precisely what the 2015 study mentioned at the outset (Chabout et al 2015) revealed: namely that the songs of mice are not, in fact, simply mechanical and repetitive, but rather vary according to complex social cues and environmental circumstances. Moreover, these ultrasonic vocalizations seem to comprise both innate and learned elements (cf.…”
Section: Who Is Squeaking?mentioning
confidence: 82%
“…In 2015, a study published in the journal Frontiers in Behavioral Neuroscience reported that not only do male mice sing songs to attract females, but that these songs are syntactically complex and vary according to social context, placing mice in the same category as songbirds (Chabout et al 2015). The principal difference is that, unlike birds, mice sing at ultrasonic frequencies (30-120 kHz), and so their songs are inaudible to the human ear.…”
Section: The Songs Of Micementioning
confidence: 99%
“…The small differences between the tracks in the proportion and number of USVs were due to our sampling of unmodified strings. This sampling method maintained the organization of multiple, rapid vocalizations, which may be important to preserve semantic information in rodents (Chabout, Sarkar, Dunson, & Jarvis, 2015; Holy & Guo, 2005). To reproduce the natural USV intensity, playback intensity of the USV tracks (measured 20 cm from the speaker) was set such that USV intensity was equivalent to recordings.…”
Section: Methodsmentioning
confidence: 99%
“…These ultrasonic vocalization (USV) syllables mostly consist of single or dual narrow-band frequency chirps with rapid frequency jumps, creating complex spectral structure (Holy and Guo, 2005; Egnor and Seagraves, 2016; Matsumoto and Okanoya, 2016). Several studies have found that mice modify their syllable content in response to different cues and social situations (Yang et al, 2013; Chabout et al, 2015; Mun et al, 2015; Gaub et al, 2016; Grimsley et al, 2016; Seagraves et al, 2016). …”
Section: Introductionmentioning
confidence: 99%